Rec. [Marco Santagata (2019). Boccaccio. Fragilità di un genio. Milano: Mondadori, 2019, 447 pp.]. - Marnoto, Rita (2020)
(2020). Rec. [Marco Santagata (2019). Boccaccio. Fragilità di un genio. Milano: Mondadori, 2019, 447 pp.]. Biblos. Revista da Faculdade de Letras da Universidade de Coimbra. , 3.ª s., 6, 215-218.